100 mm diameter rod laser amplifiers made of different Nd:glasses. (5th February 2018) - Shaykin, A A; Kuzmin, A A; Shaikin, I A; Potemkin, A K; Arbuzov, V I; Hu, Lili; Wen, Lei; Khazanov, Е A
Abstract: We measured the dependence of the weak signal gain of 100 mm diameter rod amplifiers on pump energy and transverse coordinates for four neodymium glass grades. The highest gain was obtained in N31-05 (China), and the highest radial gain uniformity in KGSS-0180 glass (Russia). The data obtained enable the optimal glass grade to be chosen for each specific problem by finding a compromise between maximum output energy and minimum distortion of beam profile.